All religion is inter-religion: engaging the work of Steven M. Wasserstrom - GhaneaBassiri, Kambiz; Robertson, Paul; Wasserstrom, Steven M. (Bloomsbury Academic, 2019)
Introducing Wasserstrom's work on religion / Kambiz GhaneaBassiri -- Nine theses on the study of religion / Steven M. Wasserstrom -- Anxiety, lament, and the language of silence: poetic redemption and gnostic / Elliot R. Wolfson -- The study of religion in a postmetaphysical age: philosophical and political reflections / Peter E. Gordon -- Taxonomy is epistemology: theorizing religion and hermeticism polythetically with Wasserstrom's theses / Paul Robertson -- Metrosophy: rereading Walter Benjamin in light of religion after religion / Jeremy F. Walton -- "La perversión de la cábala judía": Gershom Scholem and anti-Kabbalistic polemic in the Argentine Catholic nationalism of Julio Meinvielle / Jeremy P. Brown -- Before religion? The Zoroastrian concept of daena and two myths about it / Bruce Lincoln -- Nag hammadi at Eranos: rediscovering gnosticism among the historians of religions / J. Gregory Given -- Where the center of the rupture is called Judaism: Maurice Blanchot and religion after religion / Kirsten Collins -- Abrahamic encounters in the Weimar Wüste / Ruchama Johnston-Bloom -- Far too close: religion and reality in the work of Erich Auerbach and Muhammad Asad / Sam Kigar -- Is Sethian gnosticism an Abrahamic religion? Abraham, Sodom, and the parabiblical in ancient gnostic literature / Dylan M. Burns -- The repentant magician: "esoteric intimacies" and the enchantment of religious difference / Noah Salomon -- On the possibility of Jewish politics in our time: Scholem, exile, and early modern transformations / Anne Oravetz Albert -- Medieval Spanish Jews and the dangers of wealth / Andrew Berns -- Luksus and the Hasidic critique of postwar American capitalism / Michael Casper -- Epilogue: nine riddles / Steven M. Wasserstrom.